A Case Study of Pre-Service Teachers’ Enabling TPACK Knowledge: Lesson Design Projects - Agustina Tyarakanita (Hasanuddin University, 2020)
Teacher education program are expected to be able in developing pre-service teachers that capable in integrating three domains of technology, pedagogy, and content knowledge (TPACK) for future classroom practices. Every teacher program may be varied and has their own ways in developing TPACK knowledge and skill for pre-service teachers. However, the investigation of lesson design as one of instructional design resulted from the teacher program is rare especially concern on the quality of each domain within lesson design and challenges that were raised within the process of lesson plan making. Therefore, this study aims to explores the TPACK component within of pre-service teacher lesson design project of master degree of teacher education program in Indonesian University through analysing the lesson design project and conducting semi structure interview to provide the justification of determining of each component in the lesson design. The findings show that pre-service teachers’ lesson plan has been represented the domain of TPACK, but there were some domains that not showing strong representation. Also, this study found that the challenges faced by the pre-service teachers were mostly as the reason of lack teaching experiences.